Efektifitas Ekstrak Daun Nimba (Azadirachta indica) dengan Pelarut Metanol dan Air terhadap Hama Spodoptera litura F. - Hafiz Fauzana; Fifi Puspita (Jurnal Sagu, 2009)
Synthetic insecticide which is commonly used to control pest has negative impact to human health and environment. Besides, it is not effective to prevent pest. However, the usage of insecticide made of plant can provide an alternative because it has less side effects and easy degradation in nature. The Nimba plant (Azadirachta indica) is know to have insecticide element, anti-eating, and able to disturb the growth of insects. This research was carried out at the laboratory of plant protection Faculty of Agriculture and the Laboratory of Biology Faculty of Mathematics and Natural Science, Riau University. The research was carried out by factorial experiment in Completely Randomized Design with three factors, seven levels, and five replications. The three factors were the spraying of nimba leaves extract on the larvae Spodoptera litura by different solvent and water thinner which were methanol solvent and acetone thinner, methanol solvent and water thinner, and water solvent and water thinner. The treatment of each factor resulted in the different extract concentration of nimba leave. Those are 0%, 1%, 3%, 6%, 10%, 15%, and 20%. The result of research proved that nimbi leave extract using methanol solvent and acetone thinner had better result in poisoning pest. At 1% concentration level it was effective to prevent larvae S. litura which was equivalent with the concentration of 15% nimbi leave extract with methanol solvent and water thinner, and also with 20% nimbi leave extract with water solvent and water thinner.